2017
DOI: 10.1590/s1806-92902017000800006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high energy intake on carcass composition and hypothalamic gene expression in Bos indicus heifers

Abstract: -The objective of this study was to evaluate the effect of high or low energy intake on carcass composition and expression of hypothalamic genes related to the onset of puberty. Twenty-four prepubertal Nellore heifers, 18-20-months-old, with 275.3±18.0 kg body weight (BW), and 4.9±0.2 (1-9 scale) body condition score (BCS) were randomly assigned to two treatments: high-energy diet (HE) and low-energy diet (LE). Heifers were housed in two collective pens and fed diets formulated to promote average daily gain of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…According to , the NPY gene shows a strong marker significantly associated with growth and carcass traits in Hanwoo cattle. The importance of the NPY gene in cattle efficiency has been reported for different breeds, including Nelore (Santana et al, 2014;Diniz-Magalhães et al, 2017), Hanwoo , Yunling and Leiqiong , and Brahman (Cardoso et al, 2015).…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…According to , the NPY gene shows a strong marker significantly associated with growth and carcass traits in Hanwoo cattle. The importance of the NPY gene in cattle efficiency has been reported for different breeds, including Nelore (Santana et al, 2014;Diniz-Magalhães et al, 2017), Hanwoo , Yunling and Leiqiong , and Brahman (Cardoso et al, 2015).…”
Section: Tablementioning
confidence: 99%
“…The NPY gene influences several biological pathways that regulate appetite, ingestive behavior, and energy homeostasis in humans and animals Santana et al, 2014;Yu et al, 2017). Likewise, its expression is linked to increased plasma levels of insulin and corticosteroids, which mediate some actions of leptin in the hypothalamus (Anubhuti, 2006;Diniz-Magalhães et al, 2017). Several studies reported the importance of the LEP gene in animal growth, energy balance, immune system, fat deposition, reproductive traits, and heat stress (Casas and Kehrli, 2016;Foote et al, 2016;Kononoff et al, 2017;Woronuk et al, 2012).…”
Section: Introductionmentioning
confidence: 99%